Relationship between sodium–glucose cotransporter-2 inhibitors and muscle atrophy in patients with type 2 diabetes mellitus: a systematic review and meta-analysis - Xia, Chengdong; Han, Yufeng; Yin, Chunhui; Geng, Ruyue; Liu, Zhenfei; Du, Yongle; Yu, Mingkun (Frontiers in Endocrinology, 2023)
Aim: To assess the association between sodium-glucose co-transporter type-2 inhibitors (SGLT-2i) treatment and muscle atrophy in patients with type 2 diabetes mellitus (T2DM).Methods: We have searched six databases from January 1, 2012, to May 1, 2023, without language restrictions. The primary outcome was muscle mass. SThe secondary outcomes werewas weight loss, weakness, malaise, or fatigue. Subgroup analyses were performed according to the different definitions of musclemuscle metrics, treatment duration, and measurement methods. The quality of the studies was assessed usingby the Cochrane tool. The quality of evidence was assessed usingby the GRADE tool.Results: Nineteen19 RCTs involving 1,482 participants were included. Compared with the control group, meta-analysis showed that T2DM participants in the group treated with SGLT-2i had demonstrated statistically significant reductions in lean body mass of 0.66 (95% CI, -1.05 to -0.27; P=0.0009) and skeletal muscle mass of 0.35 (95% CI, -0.66 to -0.04; P=0.03). No deaths or serious adverse events were reported. The quality of evidence of the included trials was low.Conclusions: SGLT-2i may lead to a reduction in muscle strength in the treatment of T2DM compared to the control groups. However, there is still a lack of sufficient high-quality evidence to evaluate muscle atrophy due caused byto SGLT-2i.